2022
DOI: 10.3892/or.2022.8399
|View full text |Cite
|
Sign up to set email alerts
|

High expression of PDIA4 promotes malignant cell behavior and predicts reduced survival in cervical cancer

Abstract: The protein disulfide isomerase (PDI) gene family plays important roles in the maintenance of several cellular functions. Previous studies have showed that protein disulfide isomerase family A member 4 (PDIA4) is aberrantly expressed in several types of cancer, and correlates with prognosis of patients. However, the role of PDIA4 in cervical cancer remains unclear. In the present study, the expression pattern of PDIA4 from both public database and immunohistochemical analysis in cervical samples was analyzed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…There is no known direct link between autophagy and endothelial function; however, matrix proteoglycans like Decorin and Perlecan provide an indirect link [37] as both of these proteoglycans can regulate angiogenesis and autophagy [38,39]. Xing et al found that loss of PDIA-4 in cervical cancer cells significantly impaired cell proliferation and cell migration [40]. Additionally, it was found that the knockdown of PDIA-4 resulted in significantly lower cell proliferation in glioma cells [41].…”
Section: Discussionmentioning
confidence: 99%
“…There is no known direct link between autophagy and endothelial function; however, matrix proteoglycans like Decorin and Perlecan provide an indirect link [37] as both of these proteoglycans can regulate angiogenesis and autophagy [38,39]. Xing et al found that loss of PDIA-4 in cervical cancer cells significantly impaired cell proliferation and cell migration [40]. Additionally, it was found that the knockdown of PDIA-4 resulted in significantly lower cell proliferation in glioma cells [41].…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic value of vimentin expression determined in tumor cells by immunohistochemistry before treatment was previously shown using univariate and multivariate analyses of overall and disease-free survival of patients with squamous cell CC and adenocarcinoma of the uterine cervix [ 40 , 41 , 42 , 43 ]. In addition, there have been growing data on the association of other EMT markers, including the transcription factors Snail, Slug, Twist, ZEB1, etc., and EMT-related molecules with poor prognosis of long-term clinical outcome [ 43 , 44 , 45 , 46 ]; at the same time, inhibitors or negative modulators of EMT were found to be factors of favorable prognosis of CC patients [ 47 , 48 ]. Taking into account these data, it made sense to analyze the informativeness of the vimentin expression assessment in non-invasive material of scrapings from the cervix before treatment to predict the clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we, for the first time, report that loss of PDIA-4 is associated with impaired endothelial function, with reduced angiogenic potential, cell migration, and cell proliferation. Xing et al found that loss of PDIA-4 in cervical cancer cells significantly impaired cell proliferation and cell migration [44]. Additionally, it was found that the knockdown of PDIA-4 resulted in significantly lower cell proliferation in glioma cells [45].…”
Section: Discussionmentioning
confidence: 99%